2016
DOI: 10.1158/1535-7163.mct-15-0850
|View full text |Cite
|
Sign up to set email alerts
|

ERK1 as a Therapeutic Target for Dendritic Cell Vaccination against High-Grade Gliomas

Abstract: Glioma regression requires the recruitment of potent antitumor immune cells into the tumor microenvironment. Dendritic cells (DC) play a role in immune responses to these tumors. The fact that DC vaccines do not effectively combat high-grade gliomas, however, suggests that DCs need to be genetically modified specifically to promote their migration to tumor relevant sites. Previously, we identified extracellular signal-regulated kinase (ERK1) as a regulator of DC immunogenicity and brain autoimmunity. In the cu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In a different study, PFC-labeled mature human DCs were also shown to migrate from a NOD/SCID mouse thigh subcutaneous injection site to the draining popliteal lymph node within 18 h of injection [ 39 ]; immature DCs, on the contrary, did not leave the injection site. Ku and coworkers used an in situ cell labeling approach, where PFC nanoemulsion was injected intradermally and taken up by resident DCs, in an effort to visualize DCs migrating into GL261 CNS glioma tumors [ 59 ] (Table 1 ). Injection of rhodamine-conjugated PFC nanoemulsion in either wild type or Erk −/− C57BL/6 mice showed greater fluorine labeled DCs migrating into tumor tissue of Erk −/− C57BL/6 mice and as a result, slower tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…In a different study, PFC-labeled mature human DCs were also shown to migrate from a NOD/SCID mouse thigh subcutaneous injection site to the draining popliteal lymph node within 18 h of injection [ 39 ]; immature DCs, on the contrary, did not leave the injection site. Ku and coworkers used an in situ cell labeling approach, where PFC nanoemulsion was injected intradermally and taken up by resident DCs, in an effort to visualize DCs migrating into GL261 CNS glioma tumors [ 59 ] (Table 1 ). Injection of rhodamine-conjugated PFC nanoemulsion in either wild type or Erk −/− C57BL/6 mice showed greater fluorine labeled DCs migrating into tumor tissue of Erk −/− C57BL/6 mice and as a result, slower tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…CS will be particularly useful in studies that involve small amounts of 19 F, as is the case in pharmacokinetic studies 47 as well as studies involving 19 F-target-specific theranostic nanoparticles, 48 19 F/ 1 H MR smart probes, 49,50 or 19 F-labeled cells administered as therapies for tumor disease. 2,51…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressive factors expressed in DCs may contribute to this process; thus, silencing these genes could amplify the immune responses and antitumor ability of DC vaccines, and viruses are the most widely used vectors during this progress 75,76 . For example, in a murine glioma model, researchers found that signal‐regulated kinase (ERK1)‐deficient DCs appeared to show increased migration and provide survival benefits, which were proven to be associated with the increased expression of actin‐associated cytoskeletal organizing proteins and sustained Cdc42 activation 77 . So the combination of the inhibition of immune checkpoint molecules with the overexpression of TAAs or other immune activators has been tested in recent years.…”
Section: Genetically Modified DC Vaccinesmentioning
confidence: 99%